The collection - Richardson, Julie; Forbes, Brett, 1977-; Rizzotti, Patrick; Dunstan, Marcus; Melton, Patrick; McDonald, Christopher, 1955-; Stewart, Josh, 1977-; Fitzpatrick, Emma.; Tergesen, Lee.; Liddell Entertainment; Fortress Features; Lions Gate Films (Santa Monica, CA : Lions Gate Films, 2013)
When Elena is talked into attending an underground warehouse party with her friends, she finds herself caught in a nightmarish trap where the revelers are mowed, sliced, and crushed to death by a macabre series of contraptions operated by a masked psychopath.
Originally released as a motion picture in 2012.
Special features: Audio commentaries; behind-the-scenes featurettes.
Christopher McDonald, Josh Stewart, Emma Fitzpatrick, Lee Tergesen.
Rating: R; for strong bloody violence, grisly images, language and brief nudity.
DVD, widescreen presentation; 5.1 Dolby Digital.
English dialogue; English or Spanish subtitles; closed-captioned.
Keywords: Psychopaths -- Drama; Murder -- Drama; Horror films; Feature films; Video recordings for the hearing impaired